Tindak Pidana Kekerasan Seksual Inses pada Anak dalam Hukum Positif Indonesia - Azzahra, Elsya Ikhsani (Journal of Contemporary Law Studies, 2024)
The present study explores the phenomenon of incest, defined as a forbidden marital orrelational alliance wherein individuals engage in matrimonial or sexual relations due toconsanguinity or close familial ties. Incest is categorized within the realm of familial abuseor domestic violence, encapsulating acts wherein individuals coerce or compel their kin intoengaging in sexual activities. The primary objective of this research is to furnish readerswith a comprehensive comprehension of incestuous sexual violence against minors,elucidating the causative factors, typologies, repercussions on child victims, and thetherapeutic interventions available for both victims and perpetrators. Employing a legalresearch paradigm with a normative juridical research approach, this investigationprimarily relies on library studies or document analyses centered on written statutes andother legal materials. The factors contributing to incestuous incidents are discernedthrough an internal-external dichotomy, whereby internal factors pertain to thepsychological instability of the offender, and external factors relate to residing in a familialmilieu characterized by low socio-economic conditions. Children subjected to incestuoussexual violence often manifest profound behavioral alterations. Consequent adverse effectsmay include early pregnancies, with associated risks of abortion, and progeny resultingfrom incestuous unions are predisposed to heightened probabilities of physical and mentaldisabilities. Consequently, it is imperative to foster collaboration among social institutions,the community, the state, and familial units to proactively prevent and address incidentsof incestuous sexual violence.